Lack of adipocyte FAM20C improves whole body glucose homeostasis - Liping Deng; Yanshan Huang; Feifei Zhao; Puxin Chen; Xiaohong Huang (Physiological Reports, 2024)
Abstract FAM20C, a member of the family with sequence similarity 20, is involved in many physiological functions. Obesity, characterized by excessive accumulation of adipose tissue, has attracted more and more attention as a worldwide health problem. Here we generated adipocyte‐specific FAM20C knockout mice to investigate the role of FAM20C in adipose tissue expansion and obesity. Our results demonstrate that knockout mice are protected against high fat diet‐induced obesity, adiposity, and fatty liver disease. Additionally, knockout mice exhibited improved metabolic phenotypes, including enhanced glucose tolerance and insulin sensitivity compared with control mice. Furthermore, we observed reduced inflammatory infiltration and collagen deposition in the adipose tissues of knockout mice. Taken together, our results indicate that targeting FAM20C in adipocytes may be a promising strategy for the treatment of obesity and associated metabolic disorders.